(2x-2+3x)/x-0,4 = x
5x-2/x-0.4 = x / *x(x-0,4)
x(5x-2) = x(x-0,4)
5x^2-2x = x^2 - 0,4x
4x^2-1,6x = 0/:4
x^2-0,4x = 0
x(x-0,4) = 0
x = 0
x = 0,4
ответ: x1 = 0
x2 = 0,4
x не равно 0,4
(2(x-1)+3x)/x-0,4=x
(2x-2+3x)/x-0,4=x
(-x-2) / x-0,4=x
x(-x-2)=x-0,4
-x^2-2x-x+0,4=0
-x^2-3x+0,4=0
x^2+3x-0,4=0
D=9+4*0,4=10,6
x1=0,128
x2=-3,128
(2x-2+3x)/x-0,4 = x
5x-2/x-0.4 = x / *x(x-0,4)
x(5x-2) = x(x-0,4)
5x^2-2x = x^2 - 0,4x
4x^2-1,6x = 0/:4
x^2-0,4x = 0
x(x-0,4) = 0
x = 0
x = 0,4
ответ: x1 = 0
x2 = 0,4
x не равно 0,4
(2(x-1)+3x)/x-0,4=x
(2x-2+3x)/x-0,4=x
(-x-2) / x-0,4=x
x(-x-2)=x-0,4
-x^2-2x-x+0,4=0
-x^2-3x+0,4=0
x^2+3x-0,4=0
D=9+4*0,4=10,6
x1=0,128
x2=-3,128